Prevalence of Anemia and its Determinants among the Rural Women of Khyber Pakhtunkhwa-Pakistan - Naz, Shaista; Aslam, Mahnoor; Sayed, Aniqa (Annals of Human and Social Sciences, 2023)
Current study investigated prevalence of anemia and its determinants among the rural women of Khyber Pakhtunkhwa-Pakistan. Anmeia is a major public health concern in the country, however there is a lack of research studies in the rural settings. For the prevalence of anemia, 100 respondents provided blood samples and a questionnaire was also filled from each respondent. For the determinants of anemia, key informant interviews (10) from the lady doctors were conducted. It was found that more than half of the respondents were anemic as their hemoglobin was <12.0 g/dl. Socioeconomic status, cultural and gender norms, dietary factors, reproductive factors, and other factors were the important determinants of anemia among the rural women. The study calls for the developmental interventions like improved access to iron-rich foods, promotion of education and awareness, enhancement of healthcare services, and addressing of gender disparities in the study area to combat anemia.